The Effect of Job Satisfaction and Sense of Calling On the Teaching Resilience of Teachers at The Cileunyi State Special School - Irma Srimayanti; Rifqi Farisan Akbar (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Heavy workloads have been reported to cause high levels of stress among teachers in special-needs schools (SLBs) in Indonesia. Resilience enables teachers to adapt to work pressures, regulate their emotions positively, overcome difficulties, and maintain professionalism in accordance with established norms and environments as they carry out their roles as educators. This study aims to examine the effects of job satisfaction and sense of calling on teaching resilience among teachers at the Cileunyi public special-needs school (SLBN). This study uses a quantitative, sampling-based method. The research sample consisted of 55 special education teachers selected through purposive sampling, with the inclusion criterion of at least 1 year of teaching experience. Data were collected via questionnaires and analyzed using multiple linear regression. The results show that job satisfaction and sense of calling simultaneously affect teachers' teaching resilience (F = 0.000; p < 0.05), explaining 52.4% of the variance (R² = 0.524). Partially, job satisfaction did not significantly affect teachers' resilience (B = 0.124; t = 0.693; p = 0.491), whereas sense of calling had a positive effect on the resilience of special education teachers (B = 0.692; t = 4.539; p = 0.000). This shows that the meaning of calling in the teaching profession is important for building resilience in teaching. This study fulfills the research objectives but could be further developed. This shows that the meaning of calling in the teaching profession is important for building resilience in teaching. This study meets its research objectives but could be expanded to examine additional factors that may influence teachers' resilience in teaching.